STRATEGI DAN UPAYA PEMASARAN BANK SYARIAH DI INDONESIA (Studi Kasus Bank Muamalat Indonesia) - Risna Wati; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
Bank Muamalat Indonesia as a business-oriented financial institution faces very tightcompetition among Islamic banks. Their marketed products are quite similar as those of otherIslamic banks, the only difference is the socialization and marketing strategy of the products. Thepurpose of this scientific journal is obtaining the answer on how Bank Muamalat Indonesia theservice to implement the socialization and marketing strategy of the products to the public. Theresearch and the gather of data and information were carried out through conducting theinterviews and observations on several customers. Document research through literature and theinternet based on the concern of the concept of the Syariah Marketing Strategy of Bank MuamalatIndonesia. The data have been summarized, classified and analyzed using qualitative andquantitative methods. The results of how Bank Muamalat Indonesia provided information on thesocialization and use of the concept of the Syariah Marketing Strategy to its customers showedthat Bank Muamalat Indonesia still constrained by several factors that are inhibiting and cannotbe overcome, such us the education and training for the syariah marketers personal, even thoughit has been known operating for about twenty years.